Social Historiography Of Abdurrahman Wahid (Gus Dur): Collective Memory, Pesantren, And The Construction Of The Islamic Narrative Of The Nusantara - Indrawan Cahyadi; Ahmad Yunani; Muhammad Dachlan; Ahmad Suhendra; Moh. Yusni Amru Ghozali (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Abdurrahman Wahid (Gus Dur) is widely recognized as an influential Muslim intellectual whose ideas significantly shaped the discourse of Islam in Indonesia. While many studies have examined his thoughts on pluralism, democracy, and Islamic moderation, limited attention has been given to his historiographical perspective in constructing narratives of Islam in the Nusantara context. This article aims to analyze the social historiography of Abdurrahman Wahid and its role in shaping an inclusive narrative of Islam Nusantara through the intellectual tradition of pesantren and collective memory. This research employs a qualitative approach using historiographical and hermeneutic analysis of Gus Dur’s writings, speeches, and intellectual discourse. The analysis is framed within the perspectives of social historiography and collective memory to explore how historical narratives are constructed beyond elite-centered historical accounts. The findings indicate that Gus Dur’s historiographical perspective emphasizes the role of pesantren communities and marginalized social groups as active subjects in the construction of Islamic history in the Nusantara. By reinterpreting collective memory and local historical experiences, Gus Dur offers an inclusive historical narrative integrating Islamic values with local cultural traditions. This study contributes to the development of Indonesian Islamic historiography by positioning Gus Dur not only as a political and religious thinker but also as a social historian articulating a contextual and pluralistic narrative of Islam Nusantara.